Bisleuconothines B–D, Modified Eburnane–Aspidosperma Bisindole Alkaloids from Leuconotis griffithii - Nugroho, Alfarius Eko; Zhang, Wenjia; Hirasawa, Yusuke; Tang, Yiming; Wong, Chin Piow; Kaneda, Toshio; A. Hadi, A. Hamid; Morita, Hiroshi (American Chemical Society, 2018)
Three new bisindole alkaloids, bisleuconothines B-D (1-3), were isolated from the bark of Leuconotis griffithii. Their structures were elucidated by 1D and 2D NMR spectroscopy and DFT calculations. Bisleuconothine B (1) is the first monoterpene indole alkaloid dimer featuring bridges between both C-16-C-10′ and C-2-O-C-9′. All compounds were deemed noncytotoxic (IC50 > 10 μM) when tested against A549 human lung adenocarcinoma cells.